Adherence to mobile‐app‐based dietary self‐monitoring—Impact on weight loss in adults. (28th September 2021) - Payne, Jason E.; Turk, Melanie T.; Kalarchian, Melissa A.; Pellegrini, Christine A.
Abstract: Objectives: Greater dietary self‐monitoring adherence is associated with weight loss, however, the dietary self‐monitoring adherence criteria that predict weight loss are unknown. The criteria used to define adherence to dietary self‐monitoring in obesity treatment tend to vary, particularly in studies that include dietary self‐monitoring via mobile applications (apps). The objectives of this study were to (a) determine weight change outcomes related to app‐based dietary self‐monitoring and (b) determine the associations between the frequency, consistency, and completeness of dietary self‐monitoring and weight change. Methods: In this single‐arm uncontrolled prospective study, employees at a large, urban health system who had overweight or obesity self‐monitored dietary intake for 8 weeks using the Calorie Counter by FatSecret app. A paired sample t ‐test examined the association of app‐based dietary self‐monitoring and weight change; linear regression examined the associations of frequent, consistent, and complete dietary self‐monitoring and weight change. Results: A significant mean difference [ t (89) = 6.59, p < 0.001] was found between baseline and 8‐week weight ( M = −1.5 ± 2.1 kg) in the sample ( N = 90). Linear regression revealed a significant association [ F (1, 88) = 7.18, p = 0.009] between total weeks of consistent dietary self‐monitoring ( M = 4.4 ± 2.8) and percent weight loss ( M = −1.54% ± 2.26%), and a significant association [ F (1, 88) = 6.42, p = 0.013] between dietary self‐monitoring frequency ( M = 50.1% ± 33.3%) and percent weight loss. The total weeks of complete dietary self‐monitoring ( M = 3.42 ± 2.87) was not associated [ F (1, 88) = 3.57, p = 0.062] with percent weight loss. Conclusions: Consistent and frequent app‐based dietary self‐monitoring were associated with short‐term weight loss. Emphasizing these aspects of self‐monitoring may be an avenue for decreasing the burden of self‐monitoring.